2016
DOI: 10.1016/j.pss.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for understanding the DIM dust measurement at comet 67P/Churyumov–Gerasimenko

Abstract: We present a simple model for gas and dust flow from 67P/ChuryumovGerasimenko that can be used to understand the grain impact observed by the DIM instrument on Philae (Krüger et al. 2015). We show how model results when applied to the GIADA measurements Della Corte, V. et al. 2015) can be used, in conjunction with the results found by the MIRO (Schloerb et al. 2015) and VIRTIS instruments to infer surface properties such as surface temperature and surface ice fraction.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The observational evidence thus far indicates higher abundance of CO 2 from the unilluminated southern heminucleus (Hässig et al 2015) and, in particular, its depletion in Ma'at, Ash, Seth(-Hapi), and (Aten-)Babi regions in the northern hemi-nucleus where surface changes were detected (Bockelée-Morvan et al 2015;Fink et al 2016;Migliorini et al 2016). Podolak et al (2016) suggested that the measured CO 2 production rate, a few percent of water production, is insufficient to account for the typical speed of dust grains at meters per second.…”
Section: Discussionmentioning
confidence: 97%
“…The observational evidence thus far indicates higher abundance of CO 2 from the unilluminated southern heminucleus (Hässig et al 2015) and, in particular, its depletion in Ma'at, Ash, Seth(-Hapi), and (Aten-)Babi regions in the northern hemi-nucleus where surface changes were detected (Bockelée-Morvan et al 2015;Fink et al 2016;Migliorini et al 2016). Podolak et al (2016) suggested that the measured CO 2 production rate, a few percent of water production, is insufficient to account for the typical speed of dust grains at meters per second.…”
Section: Discussionmentioning
confidence: 97%
“…They are consistent with a particle radius of 0.9 mm, density of 250 kg m −3 , and porosity close to 90 %. Data and estimations also indicate that the particle likely moved at near 4 m s −1 with respect to the comet (Podolak et al 2016;Flandes et al 2018).…”
Section: Dimmentioning
confidence: 90%
“…if using C d ∼ 4/3 (Epstein 1924;Podolak et al 2016) for spherical dust particles. For present-day Phaethon, considering a maximum surface temperature of ∼800 K near perihelion, but a steady mean gas flux of J s <∼ 3 × 10 17 m −2 s −1 , the critical radius b max is only about 1.8 μm.…”
Section: Dust Accelerationmentioning
confidence: 99%